Green Synthesis of IONPs for Photocatalytic Activities - A. Khamees, Husam; A. Abid, Muslim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2022)
To make iron oxide nanoparticles (IONPs), a simple chemical approach was used to combine iron chloride (FeCl2+FeCl3) salt with onion peel extract. According to the study, iron salts can be converted into IONPs by the biomolecules in onion peel extract. From FeCl2+FeCl3 to γ -Fe2O3, the approach changes iron oxide NPs' size, shape, purity and phases. In water treatment, γ -Fe2O3 NPs are critical for the removal of the color methylene blue (MB). X-ray diffraction (XRD), scanning electron microscopy (SEM), ultraviolet (UV-Vis) and photoluminescence (PL) spectroscopy were used to identify IONPs. Results from the XRD experiment showed crystals having a tetragonal structure have average size of 13.4680 nm for γ- Fe2O3 NPs with a chemical method. Tetragonal diffraction peaks were observed in the data, and excellent crystal quality in a cubic shape. In the simple chemical process, the grain size was around (23.9 to 169.4) nm and average grain size 76.6 nm. UV-VIS measurements showed that the energy gap value had shifted to the blue from 1.94 to 2.96 eV in the simple chemical method.PL spectroscopy showed that the near band edge emission of γ-Fe2O3 NPs with a simple chemical approach was roughly 2.65 eV. NPs photocatalytic activity was as evidenced by the breakdown of MB dye when exposed to a moderate amount of light, as shown in this study. The results show that the synthesized material is of high quality γ-Fe2O3 NPs, with greater degrading efficiency when made using a simple chemical method, reaching 89.2% at 75 minutesfor 3 mg and 91.1% at 150 minutes for 5 mg, with a high level of photocatalytic efficacy the γ-Fe2O3.